The Effect of Interest Rates, Exchange Rates, and Inflation on Stock Prices, Moderated by CAR (A Study of the Banking Industry on the Indonesia Stock Exchange, 2021–2025) - Maria Ratna Marisa Ginting; Muchlis Mas’ud; Darmoko; Hanif Rani Iswari; Survival (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze and examine the influence of macroeconomic factors, consisting of Interest Rates, Exchange Rates, and Inflation, on Stock Prices in banking sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2025 period. Furthermore, this study also examines the role of the Capital Adequacy Ratio (CAR) as a moderating variable in moderating the effects of interest rates, exchange rates, and inflation on these stock prices. The research method employed is an explanatory research approach with an ex post facto design. The population in this study comprises all banking companies listed on the IDX during the 2021–2025 period. The sampling technique utilizes a purposive sampling method based on specific criteria, resulting in a sample of 44 banking companies for observation. The data used are secondary data, including annual financial statements and official macroeconomic indicator data. The data analysis method applies Panel Data Regression Analysis with a Moderated Regression Analysis (MRA) approach, processed using EViews 14 statistical software. The results of the study indicate that: 1) Interest Rates have a negative and significant effect on Stock Prices. 2) Exchange Rates have a positive and significant effect on Stock Prices. 3) Inflation has a positive and significant effect on Stock Prices. 4) CAR is able to moderate the effect of Interest Rates on Stock Prices, classified as a Pure Moderator. 5) CAR is unable to moderate the effect of Exchange Rates on Stock Prices, classified as a Predictor Moderator. 6) CAR is able to moderate the effect of Inflation on Stock Prices, classified as a Quasi Moderator in the banking industry on the IDX for the 2021–2025 period.